Augmented Reality Design of Indonesia Fruit Recognition - Dewi Agushinta R.; Ihsan Jatnika; Henny Medyawati; Hustinawaty Hustinawaty (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Augmented Reality (AR) is one of the popular technologies nowadays. Along with the technological advances, Augmented Reality is an effort to combine the real world and virtual worlds created through computers so that the boundary between the two becomes very thin because Augmented Reality allows users to interact in real-time with the system. Augmented Reality can be applied in various fields according to the needs of each user. One application is on Android-based mobile hardware applications. This research developed the Augmented Reality battle with some of the features more interactive, interesting and clearer information to facilitate the user in its operation. This Augmented Reality is applied to the Android mobile device with the name of FruitGarden. This paper presented of designing Augmented Reality for recognizing the fruit of Indonesia archipelago which will give a different view of performing the fruit image and information.